Bed Rest and Hypoxic Exposure Affect Sleep Architecture and Breathing Stability - Morrison, Shawnda A.; Mirnik, Dani; Korsic, Spela; Eiken, Ola; Mekjavic, Igor B.; Dolenc-Groselj, Leja (Frontiers in Physiology, 2017)
Abstract Objective Despite over 50 years of research on the physiological effects of sustained bed rest, data characterising its effects on sleep macrostructure and breathing stability in humans are scarce. This study was conducted to determine the effects of continuous exposure to hypoxia and sustained best rest, both individually and combined, on nocturnal sleep and breathing stability. Methods Eleven participants completed three randomised, counter-balanced, 21-day trials of: (1) normoxic bed rest (NBR, PIO2=133.1±0.3), (2) hypoxic ambulatory confinement (HAMB, PIO2= 90.0±0.4) and (3) hypoxic bed rest (HBR, PIO2= 90.0±0.4; ~4,000 m equivalent altitude). Full objective polysomnography was performed at baseline, on Night 1 and Night 21 in each condition. Results In NBR Night 1, more time was spent in light sleep (10±2%) compared to baseline (8±2%; p=0.028); Slow-wave sleep was reduced from baseline in the hypoxic-only trial by 18% (HAMB Night 21, p=0.028) and further reduced by 33% (HBR Night 1, p=0.010), and 36% (HBR Night 21, p=0.008) when combined with bed rest. The apnoea-hypopnea index doubled from Night 1 to Night 21 in HBR (32 to 62 events∙h-1) and HAMB (31 to 59 events∙h-1; p=0.002). Those who experienced greatest breathing instability from Night 1 to Night 21 (NBR) were correlated to unchanged or higher (+1%) night SpO2 concentrations (R2=0.471, p=0.020). Conclusion Bed rest negatively affects sleep macrostructure, increases the apnoea-hypopnoea index, and worsens breathing stability, each independently exacerbated by continuous exposure to hypoxia.